ANALISIS BENTUK DAN MAKNA SYAIR LAGU GEREJA KRISTEN DALAM BUKU NYANYIAN PUJIAN DI GEREJA BAPTIS INDONESIA WANAMUKTI SEMARANG (Universitas Negeri Semarang, 2016)
The researcher wants to know about the form and purpose of the ryhme of those songs that still being used at GBI Wanamukti, the problem formulation of this research are : (1). what type of song structure analysis of The Book of Nyanyian Pujian that is still being used at GBI Wanamukti Semarang? (2). what is the meaning that lies behind the rhyme in The Book of Nyanyian Pujian that is still being used at GBI Wanamukti Semarang?. The researcher used Qualitative Descriptive as the research method. The result of this research aim to know that